Pengaruh Terapi Slow Stroke Back Massage (SSBM) terhadap Depresi pada Lansia di Unit Pelayanan Teknis Panti Sosial Lanjut Usia (UPT PSLU) Kabupaten Jember. (The Effect of Slow Stroke Back Massage (SSBM)Therapy for Depression in Elderly in Unit Pelayanan T - Aris Kurniawan; Wantiyah Wantiyah; Kushariyadi Kushariyadi (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Depression is a psychiatric disorder focused on the natural feelings of an individual, characterizedby prolonged sadness, feelings of failure and worthlessness along with other accompanyingsymptoms. Depression in the elderly is caused by several factors, (physiological factors andpsychological factors). The physiological factors is dysregulation of neurotransmitters. SSBMtherapy produce the endorphin to anticipate dysregulation of neurotransmitters that causedepression in elderly. The objective of this research was to know the effect of SSBM for depressionof elderly in UPT PSLU Jember. This research was a quasy experiment with pretest-posttest withcontrol group design. The respondent is 20 respondents, conducted by simple random sampling,and divided into two groups: treatment and control group. Data were analyzed used t test dependentand t-test independent with α: 0,05 . The result showed that there were significant differences ofdepression in treatment group (p value: 0,001). Otherwise, there were no differences of depressionin control group (p value: 1,000). Furthermore, there were significant differences of depressionbetween treatment group and control group after SSBM (p value: 0,027). The conclusion is SSBMcan decrease depression in elderly. It is recommended for nurses to do SSBM to decreasedepression in elderly.Keywords: SSBM, depression, elderly